Caspase-11 drives macrophage hyperinflammation in models of Polg-related mitochondrial disease - Jordyn J. VanPortfliet; Yuanjiu Lei; Muthumeena Ramanathan; Camila Guerra Martinez; Jessica Wong; Tim J. Stodola; Brian R. Hoffmann; Kathryn Pflug; Raquel Sitcheran; Stephen C. Kneeland; Stephen A. Murray; Peter. J. McGuire; et al. (Nature Communications)
Abstract Mitochondrial diseases (MtD) represent a significant public health challenge due to their heterogenous clinical presentation, often severe and progressive symptoms, and lack of effective therapies. Environmental exposures, such bacterial and viral infection, can further compromise mitochondrial function and exacerbate the progression of MtD. However, the underlying immune alterations that enhance immunopathology in MtD remain unclear. Here we employ in vitro and in vivo approaches to clarify the molecular and cellular basis for innate immune hyperactivity in models of polymerase gamma (Polg)-related MtD. We reveal that type I interferon (IFN-I)-mediated upregulation of caspase-11 and guanylate-binding proteins (GBP) increase macrophage sensing of the opportunistic microbe Pseudomonas aeruginosa (PA) in Polg mutant mice. Furthermore, we show that excessive cytokine secretion and activation of pyroptotic cell death pathways contribute to lung inflammation and morbidity after infection with PA. Our work provides a mechanistic framework for understanding innate immune dysregulation in MtD and reveals potential targets for limiting infection- and inflammation-related complications in Polg-related MtD.